2021
DOI: 10.1109/jstars.2021.3098678
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Multispectral Satellite Image Segmentation for Water Body Detection

Abstract: Automated water body detection from satellite imagery is a fundamental stage for urban hydrological studies. In recent years, various deep convolutional neural network (DCNN)-based methods have been proposed to segment remote sensing data collected by conventional RGB or multi-spectral imagery for such studies. However, how to effectively explore the wider spectrum bands of multi-spectral sensors to achieve significantly better performance compared to the use of only RGB bands has been left underexplored. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…The results of the experiments that utilize multispectral input types are provided in Table IV. Even though there are a number of band fusion modules applied by slightly modifying the networks [104], [105], the motivation in this study is to implement only the original architectures so only U-Net, SegNet, and random forest are used. Although tested for a limited number of architectures, the results are consistent with three-channel input type experiments.…”
Section: B Resultsmentioning
confidence: 99%
“…The results of the experiments that utilize multispectral input types are provided in Table IV. Even though there are a number of band fusion modules applied by slightly modifying the networks [104], [105], the motivation in this study is to implement only the original architectures so only U-Net, SegNet, and random forest are used. Although tested for a limited number of architectures, the results are consistent with three-channel input type experiments.…”
Section: B Resultsmentioning
confidence: 99%
“…RGB band imagery is the primary focus in substantial research for water body extraction, but many more bands are available in RS imagery. A multichannel water body detection network (MC-WBDN) was created in [ 47 ], which fused the infrared and RGB channels and used them as input data for their CNN architecture. They demonstrated that when multispectral data is used, model performance for water body detection is increased and the model is more robust to lighting conditions.…”
Section: The State Of the Art: Advances In Intelligent Waterbody Info...mentioning
confidence: 99%
“…(Corresponding author: Guizhou Zheng.) Y. Zhao, G. Zheng, Z. Xu, and Z. Chen are with the School of Geography and Information Engineering, China University of Geosciences, Wuhan segmentation is to divide each pixel unit in HRRSIs into corresponding categories, which holds great significance in applications such as land use and land cover [2], [3], ecological system [4], [5], inversion of water depth [6], [7] and other industries. However, visual interpretation of HRRSIs is a method with low efficiency and strong dependence on knowledge and experience.…”
Section: Introductionmentioning
confidence: 99%